The Effects of Systemic Banking Crises in the Inter-War Period - Bruno Rocha; Solomos Solomou (Center for Economic Studies and ifo Institute (CESifo), 2015)
This paper examines the time-profile of the impact of systemic banking crises on GDP and industrial production using a panel of 24 countries over the inter-war period and compares this to the post-war experience of these countries. We show that banking crises have effects that induce medium-term adjustments on economies. Focusing on an eight-year horizon, it is clear that the negative effects of systemic banking crises last over the entirety of this time-horizon. The effect has been identified for GDP and industrial production. The adverse effect on the industrial sector stands out as being substantially larger in magnitude relative to the macroeconomic effect. Comparing the results across long-run historical periods for the same selection of countries and variables identifies some differences that stand out: the short term macroeconomic impact effects are much larger in the post-war period, suggesting that the propagation channels of shocks operate at a faster pace in the more recent period. Moreover, the time-profile of effects differs, suggesting that modern policies may be modulating the temporal shape of the response to banking crises shocks. However, the broad magnitude of the adverse effect of banking crises remains comparable across these time periods.
Keywords: E60; N00; N20; G01; 330; local projections; banking crises; financial crises; economic history; inter-war